Revisiting the Solubility-Permeability Relationship with Hydrophobic Drug Umifenovir in Pluronic Solutions: Impact of pH and Co-Solvent - Tatyana Volkova; Olga Simonova; German Perlovich (MDPI AG, 2023)
This study describes the influence of pluronic F-127 (F-127) and ethanol (EtOH) on the solubility of umifenovir (UMF) in buffer solutions of pH 2.0 and pH 7.4, and its permeability through cellulose membranes. A 44.4-fold greater UMF solubility in acidic medium as compared to an alkaline one was estimated at 310.15 K. The concentration of UMF in the saturated solution was enhanced by the interaction with F-127 micelles. The combined positive effect of EtOH and F-127 on the solubility was estimated. The aggregation number of F-127 micelles in the presence of 10% and 20% ethanol appeared to be reduced by 2.1-fold and 4.1-fold, respectively, as compared to buffer pH 7.4. The presence of ethanol in buffer pH 7.4 solution provided better solvent conditions but inhibited the formation of F-127 micelles. The impact of UMF on the aggregation number of F-127 was not pronounced and was expressed only by a slight increase of 1 and 3 units in 10% and 20% EtOH, respectively. According to the values of zeta potential, addition of EtOH reduced the stability of the system. The permeation of UMF in buffer pH 7.4 measured through the cellulose membrane MWCO 12-14 kDa was increased 1.4-fold by 10% EtOH. An increase in EtOH content to 20% reduced this effect to 1.2-fold. Decreasing effect of 1.5% F-127 on the permeability was inhibited by using 10% EtOH. The solution containing 1.5% F-127 and 10% EtOH was shown to be an advantageous system for UMF in view of the solubility-permeability balance. The authors suppose the findings of the study to be useful for the design of pharmaceutical formulations based on UMF antiviral drugs.